Russians among the Peoples of the Baltic States: the Origins of Mutual Perceptions and Relations - Simonyan, R. H.; Kochegarova, T. M. (Vestnik MGIMO-Universiteta, 2015)
The Baltic countries - the next neighbors of Russia, whose history is closely linked with our country in the period of Kievan Rus, the Grand Duchy of Moscow, the Russian Empire, the Soviet Union, and today in a broad European context. Both Russia and the Baltic states are the states that make up the Baltic region. The role of this region in the European integration is the key. The border between Russia and the European Union, Russia and the EU are in direct contact, there is a direct interaction between the peoples of Europe, divided by confrontations of the twentieth century. In this border area sociocultural diffusion occurs between the two parts of the European continent. Factor of cooperation of neighbors is an essential guarantee of stability of the world system. For this cooperation to be productive, you must have an adequate view of the neighbors, about the processes that take place there. Knowing immediate environment in a globalized world is a prerequisite for good neighborly relations. The condition of willingness to help, if needed. In the current civilization elevated risk mutual definitely be in demand. Historical experience shows that the lack of objective knowledge is the cause of misunderstanding, and often the source of origin of enmity. This is not only of interest to neighboring nations, but the need to have certain knowledge about them, are closely linked to historical responsibility. Feature stories is that it is inextricably linked with modernity. For public decision-making needs of reliable knowledge about the processes that led to the present, the historical conditions of social psychology folding neighboring nations, forms of expression of their national characteristics. On the basis of sociological methods - from the study of documentary and literary sources, analysis of the results of mass surveys to group discussions and participant observation - analyzes the problems of mutual Russian and Baltic peoples.